Single dose Dexamethasone versus multi-dose Prednisolone in prevention of exacerbation and relapse in Asthmatic children; A RANDOMIZED CONTROLLED TRIAL - Tariq Mehmood , Tariq Saeed , Muhammad Nasir , Israr Liaquat , Shaukat Hussain , Muhammad Hafeez , Tariq Mehmood , Tariq Saeed , Muhammad Nasir , Israr Liaquat , Shaukat Hussain , Muhammad Hafeez (Journal of Rawalpindi Medical College, 2019)
Introduction: Asthma is a common chronic inflammatory disease of the airways characterized by reversible airflow obstruction, and bronchospasm. The first line of treatment in the management of acute asthma is inhaled beta 2 agonists (salbutamol). This study is design to determine the effectiveness of i/v dexamethasone compared to oral prednisolone in asthmatic children in preventing exacerbation and relapse. It may be more helpful in improving the quality of life of asthmatic children being a better convenient treatment modality. Aim: to compare the frequency of relapse of asthma with dexamethasone and prednisolone in treatment of asthma exacerbations in children. Subject and Methods: this is a randomized controlled trial conducted atICU of Paediatric Department, Holy Family Hospital from 16th March 2016 to 15th September 2016.468 patients with an asthma exacerbation were selected in this study. Patients were randomly allocated into two groups. A total 234 patients in group A were treated with single IV dose Dexamethasone and 234 in group B was treated with oral prednisolone. Baseline characteristics of children were recorded in the structured proforma along with the signs and symptoms assessed through history, physical examination and PRAM Scoring. After treatment and assessment, the patients were discharged on day 5 and they were called back by the end of 2 weeks for final follow up visit. In case of any relapse they were clearly instructed to immediately return to hospital that was recorded. Results: The average age of the children 3.31±0.97 years. There were 173(37%) female and 295(63%) male. Rate of relapse was significantly low in group A as compare to group B (9.8% vs. 17.9% p=0.011). Conclusion: it is concluded that dexamethasone is an effective alternative to prednisone in the treatment of moderate acute asthma exacerbations in children, with the added benefits of improved compliance and cost.